2012
DOI: 10.5704/moj.1211.002
|View full text |Cite
|
Sign up to set email alerts
|

Clubfoot: The Treatment Outcome Using Quantitative Assessment of Deformity

Abstract: Clubfoot, outcome, treatment, quantitative assessment, deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…In our study, the number of boys was close to three times the number of girls, with a ratio of 2.8:1. This is contrary to local studies conducted by Boo 9 and Rasit 10 that showed equal number of patients between the two genders. However, studies from Sweden 12 and West Australia 13 reported male predominance with the ratio of 2.4 and 2.0 to 1 respectively.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In our study, the number of boys was close to three times the number of girls, with a ratio of 2.8:1. This is contrary to local studies conducted by Boo 9 and Rasit 10 that showed equal number of patients between the two genders. However, studies from Sweden 12 and West Australia 13 reported male predominance with the ratio of 2.4 and 2.0 to 1 respectively.…”
Section: Discussioncontrasting
confidence: 96%
“…We had more right sided (71%) unilateral clubfoot. In the literature, Byron 14 and Wallander 12 reported that right unilateral clubfoot was more common, while other studies by Boo 9 and Rasit 10 reported that the left side was more commonly affected.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was no difference in patients with LLD; however, the LLD measurement was only of the tibial length and excluded the foot vertical length. 32 One of the main questions raised by this study is whether the clubfoot is worse because of LLD or if having an LLD results in an equinus gait and increases the risk of relapse. We believe that both assumptions are likely true.…”
Section: Discussionmentioning
confidence: 94%
“…14 Rasit et al used Quantitative Clubfoot Assessment of Deformity (QCAD) for assessing outcomes of clubfoot treatment based on Pirani deformity severity score and anthropometric measurement includes leg length, mid-leg circumference, foot length and mid-foot circumference. 15 The Bangla Tool, developed in Bangladesh, evaluated results of clubfoot management as a tool that was quick, relevant and reliable for use in children of walking age who present to clubfoot clinics. 16 Three areas of examination are included: parent satisfaction, gait, clinical examination of the clubfoot.…”
Section: Discussionmentioning
confidence: 99%